The True Beauty Behind the Phantom’s Mask in Andrew Lloyd Webber’s The Phantom of the Opera - Dina Natasya; M. Misbahul Amri; Mochamad Nasrul Chotib (Soshum: Jurnal Sosial dan Humaniora, 2025)
The Phantom of the Opera is a novel by Gaston Leroux that has been adapted into plays and films. The adaptation of the novel in the play is still being staged in several theatres overseas this year. The best play adaptation is Andrew Lloyd Webber’s Phantom of the Opera (1986) because it became the longest-running theatrical event in Broadway history. The neat appearance of the play cannot be separated from the reference play script, which explains all the intrinsic elements. The mask that characterises the Phantom’s appearance holds a paradoxical meaning for the beauty he desires to get compassion. Therefore, the following study aims to explore the paradox of the mask as a metaphorical symbol worn by the Phantom from a close reading approach. The analysis is based on the play The Phantom of the Opera by Andrew Lloyd Webber. The metaphorical symbol of the mask is discovered by analysing the narrated details and related dialogue conversations. Then, its intensity directly connects with the paradoxical meaning that using a mask to cover up deformity hides true beauty. Thus, it can be concluded that covering something does not always make it good, and the thing covered is a good object without realising it. This study is expected to increase awareness and open new perspectives that previously defined the Phantom’s appearance as hideous, but it turns out that it contains beauty.